2020
DOI: 10.1017/s1368980020003432
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of dietary and physical activity behaviours among women of reproductive age in urban Uganda, a qualitative study

Abstract: Objective: To explore determinants of dietary and physical activity behaviours among women of reproductive age. Design: Data were collected through focus group discussions (FGD). The FGD guide was based on a modified theoretical framework; theory of planned behaviour was incorporated with constructs of health belief model, precaution adoption process model, social cognitive and social support theory. Discussions were audio recorded, transcribed verbatim and analysed thematically. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(57 citation statements)
references
References 54 publications
2
54
0
Order By: Relevance
“…We found no articles using the term 'food literacy' published by first authors based in low-income countries, which has been attributed to limited research budgets, low salaries, poor infrastructure and facilities and political instability [39]. However, since our search was conducted, articles from Ethiopia [40] and Uganda [41] have been published, further highlighting the relevance of the term.…”
Section: Consensus On Definitions and Conceptualisationsmentioning
confidence: 88%
“…We found no articles using the term 'food literacy' published by first authors based in low-income countries, which has been attributed to limited research budgets, low salaries, poor infrastructure and facilities and political instability [39]. However, since our search was conducted, articles from Ethiopia [40] and Uganda [41] have been published, further highlighting the relevance of the term.…”
Section: Consensus On Definitions and Conceptualisationsmentioning
confidence: 88%
“…Participants reported that food safety during meal preparation was important to keep their families safe (Kendall et al, 2019;Knight et al, 2003;Pham and Turner, 2020;. Participants' actual or perceived knowledge of how foods are produced influenced food preparation and storage practices at home (Lagerkvist et al, 2018;Li et al, 2018;Nago et al, 2012;Wertheim-Heck et al, 2014;Yiga et al, 2020).…”
Section: Food Safety Factors Influencing Food Preparation and Storage...mentioning
confidence: 99%
“…Participants reported that cooking vegetables was time consuming and difficult, due to the preparation methods required to ensure safety, but pre-packaged vegetables from vendors were not prioritized as they were also deemed to be unhygienic (Yiga et al, 2020). One study in Vietnam demonstrated that social factors, such as an established relationship with vegetable vendors, could reduce time spent on food preparation at home: "If the seller has already washed the vegetables, I even don't have to do that myself" [Adult, Vietnam] ( Wertheim-Heck et al, 2014).…”
Section: Food Safety Factors Influencing Food Preparation and Storage...mentioning
confidence: 99%
“…Four qualitative studies looked at community solutions to malnutrition in a novel and participatory approach with the population (13)(14)(15)(16) , while one study looked at factors influencing the implementation of a multisectoral, community-level nutrition programme aimed at improving infant and young child feeding practices (17) . The other qualitative studies explored nutritionrelated behaviours of mothers (18,19) , women outside of their maternal role (20) , parents (21) , and adolescents (22) .…”
mentioning
confidence: 99%
“…The conflict between traditional knowledge on infant feeding and information provided by health workers is also highlighted in a study in Rwanda (19) . The importance of social media as source of nutrition information and determinant of food choices is reflected in a study in Ghana (20) . In a study in South Africa, parents noted that preschool children even at this very young age are drawn to devices such as smartphones, tablets and laptops and that TV was regularly watched; these habits may limit physical activity, thereby favouring overweight (21) .…”
mentioning
confidence: 99%